THE INFLUENCE OF HORAY LEARNING MODEL ASSISTED BY VIDEO MEDIA ON STUDENTS’ LEARNING OUTCOMES - Ayu Alamiah; Marleni Marleni; Henni Riyanti (Universitas PGRI Palembang, 2024)
This research aims to determine the effect of the Course Review Horay learning model using video media on science learning outcomes for class IV at SD Negeri 43 Palembang. This research uses an experimental method with a quasi-experimental design, namely nonequivalent control group design. The population in this research was 42 class IV students and the research sample of 42 was taken using a nonprobability sampling technique. Data collection used tests with data analysis using the Independent Sample t Test with the help of SPSS version 25. The results of the study showed that there was an influence of the course review horay learning model on the science learning outcomes of class 4 students at SD Negeri 43 Palembang. In the Independent Sample t Test testing was obtained. Sig value (2-tailed) 0.020 < 0.05. Thus, it can be concluded that there is a significant influence of the use of the Horay course review model on the science learning outcomes of class IV at SD Negeri 43 Palembang